A Meta-Analysis Of The Relations Between Psycological Capital And Work Engagement - Lista Meria; Saukani Saukani (Fakultas Ekonomi Universitas Indonesia Timur, 2022)
Studies related to the relationship between psychological capital and work engagement have been carried out in previous studies in various contexts. The aim of this study is to conduct a meta-analytic of the empirical study of psychological capital models in the field of management. Meta-analysis was carried out through article searches from the ScienceDirect, Emerald Insight, Proquest, Sage, Google Scholar databases of 17 research articles that were selected and thoroughly analyzed. The results reveal that psychological capital has a positive and significant relationship with work engagement. This research provides promotion for managerial and practice and recommends further research that can be explored.